2021
DOI: 10.1111/jcmm.16813
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different intensities of continuous training on vascular inflammation and oxidative stress in spontaneously hypertensive rats

Abstract: We aimed to study the effects and underlying mechanism of different intensities of continuous training (CT) on vascular inflammation and oxidative stress in spontaneously hypertensive rats (SHR). Rats were divided into five groups (n = 12): Wistar‐Kyoto rats sedentary group (WKY‐S), sedentary group (SHR‐S), low‐intensity CT group (SHR‐L), medium‐intensity CT group (SHR‐M) and high‐intensity CT group (SHR‐H). Changes in body mass, heart rate and blood pressure were recorded. The rats were euthanized after 14 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…However, the effect magnitude will depend on exercise intensity, duration, glycogen availability, and training status (57). Interestingly, highintensity training did not improve AMPK activation in hypertensive rats, which contrasts with low-and mediumintensity exercise (58).…”
Section: Covid-19-related Inflammatory Pathways Modulated By Irisin A...mentioning
confidence: 95%
See 1 more Smart Citation
“…However, the effect magnitude will depend on exercise intensity, duration, glycogen availability, and training status (57). Interestingly, highintensity training did not improve AMPK activation in hypertensive rats, which contrasts with low-and mediumintensity exercise (58).…”
Section: Covid-19-related Inflammatory Pathways Modulated By Irisin A...mentioning
confidence: 95%
“…Also, proinflammatory cytokines may trigger TLR4/MyD88/NF-kB pathways activation, contributing to hypertensive response in the hypothalamus (103). Considering exercise effects on hypertension, low-and mediumintensity exercise effectively improved blood pressure through TLR4/NF-kB suppression (58) and improved hypertension in rats (103). Exercise modulates TLR4 and NF-kB expressions, depending on the training intensity: acute, moderate, low, and on the training frequency: acute and regular (104).…”
Section: Toll-like Receptor 4/myd88 Pathwaymentioning
confidence: 99%
“…This study revealed that continuous aerobic exercise had positive effect on oxidative stress and renal dysfunction in SHR. Both low intensity and medium intensity could improve the renal dysfunction and the oxidative stress of SHR, while our previous research found adverse effects of HICT on blood pressure and oxidative stress ( 36 ). A key finding was observed in this research: Both low intensity and medium intensity could significantly improve the renal dysfuntion of SHR, while medium intensity showed a better effect.…”
Section: Discussionmentioning
confidence: 81%
“…Exercise protocols were performed on a treadmill (SA101C; SANS Biological Technology, Jiangsu, China) customized to research sports physiology and pathology characteristics of small experimental animals (220 V, 50 Hz; 8 trails for running; speed control 0–100 m/min with a resolution of 0.01 m/min) and connected to a treadmill-software for continuous speed monitoring ( 36 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation